PELATIHAN INOVASI PRODUK DAN PENGEMBANGAN BISNIS UMKM UNTUK MENAMBAH NILAI JUAL DAN DAYA SAING PASAR LOKAL: Product Innovation And MSME Business Development To Increase Selling Value And Local Market Competitiveness - Aminullah, Aminullah; Hamid, Hamid; Sativa, Denianto Yoga; Marini, Ida Ayu Ketut; Apriani, Titin; Sari, Ni Luh Ariningsih; Listyaningrum, Novita; Sari, Arlina Maya; Agustiawan, Dedi (Yayasan Al-Amin Qalbu, 2025)
This Community Service (PKM) program aims to provide training to the community for product innovation and MSME business development to increase sales value and local market competitiveness in Meninting Village, West Lombok Regency. The method for implementing the community service program is